Catalytic Hydrodeoxygenation of High Carbon Furylmethanes to Renewable Jet‐fuel Ranged Alkanes over a Rhenium‐Modified Iridium Catalyst. Issue 16 (16th August 2017) - Liu, Sibao; Dutta, Saikat; Zheng, Weiqing; Gould, Nicholas S.; Cheng, Ziwei; Xu, Bingjun; Saha, Basudeb; Vlachos, Dionisios G.
Abstract: Invited for this month′s cover is the group of Basudeb Saha and Dionisios G. Vlachos at the Catalysis Center for Energy Innovation (CCEI), University of Delaware. The image shows the use of renewable aviation fuels produced from C−C coupled biomass platforms. The Full Paper itself is available at10.1002/cssc.201700863 . Abstract : "Production of renewable materials is one of the most important topics in biorefineries…" This and more about the story behind the research that inspired the Cover image is presented in the Cover Profile. Read the full text of the corresponding research at10.1002/cssc.201700863 . View the Front Cover here:10.1002/cssc.201701481 .